Museo Interactivo del Turismo Tolimense (2022)
The municipality of Melgar over the years has become a nationally recognized tourist destination, although the planning was unorthodox, it has developed optimally due to its strategic location, its climatic conditions, landscapes and recreation and rest areas it offers. Melgar has been building its tourist identity, since after the arrival of tourist facilities, hotels and restaurants, many of its inhabitants left the countryside and dedicated themselves to take advantage of the commercial demands of the new tourism, while others sold their land to outside investors who saw the vacation potential of the region.